Piłka nożna, styl życia i procesy reprodukcji kulturowej w Stanach Zjednoczonych - Melosik, Zbyszko (Wydawnictwo Naukowe UAM, 2016)
In his article the author considers the paradox of soccer appropriation in the United States. It is rejected by majority of Americans at the professional level as they prefer football, basketball and baseball. However, at the recreational level soccer is used by middle class and upper middle class as a form of their status confirmation and for cultural reproduction. The symbol of such an approach is analysed – the „soccer mom” as a person who considers soccer as a very valuable exercise experience for her daughters and sons.
Soccer, Lifestyle and the Process of Cultural Reproduction in the United States of America
Keywords: soccer; lifestyle; middle class; recreation; cultural reproduction; soccer mom